2020
DOI: 10.1155/2020/5346573
|View full text |Cite
|
Sign up to set email alerts
|

miR-7-5p Promotes Hepatic Stellate Cell Activation by Targeting Fibroblast Growth Factor Receptor 4

Abstract: Aims. Fibroblast growth factor receptor 4 (FGFR4) is a key mediator that protects the liver from chronic injury. MicroRNA-7 (miR-7) is a tumor suppressor and associated with lipid homeostasis in the liver. This study was designed to examine the role of the miR-7-5p/FGFR4 axis in liver fibrogenesis. Methods. TargetScan was employed to predict microRNAs that targeted FGFR4 on the 3′-untranslated region (3′-UTR). miR-7-5p and FGFR4 expression in pathological liver tissues and LX-2 cells was determined using qRT-P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 36 publications
1
4
0
Order By: Relevance
“…We found that the level of miR-7-5p expression also correlates with the degree of in-filtration of the PCa tissue by tumor-associated macrophages. These facts are consistent with the literature data [32,33] and allow us to assert the participation of these miRNAs in the formation T. Borikun, O. Mushii, A. Pavlova, T. Burda, T. Zadvornyi of the TME of PCa. Along with this, the study [34] has demonstrated that miR-7-5p participates in the processes of hyaluronan-dependent differentiation of fibroblasts by inhibiting EGFR signaling.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the level of miR-7-5p expression also correlates with the degree of in-filtration of the PCa tissue by tumor-associated macrophages. These facts are consistent with the literature data [32,33] and allow us to assert the participation of these miRNAs in the formation T. Borikun, O. Mushii, A. Pavlova, T. Burda, T. Zadvornyi of the TME of PCa. Along with this, the study [34] has demonstrated that miR-7-5p participates in the processes of hyaluronan-dependent differentiation of fibroblasts by inhibiting EGFR signaling.…”
Section: Discussionsupporting
confidence: 92%
“…miR-7-5p is involved in multiple disease models by regulating the targeted genes. It has been reported that miR-7-5p enhances activation of hepatic stellate cell by regulating fibroblast growth factor receptor 4 [ 27 ]. miR-7-5p modulates brain edema after intracerebral hemorrhage [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many genes specifically increase related transcriptional activities and regulate a series of metabolic activities in the body during longterm adaptation to hypoxic environments. MiR-7-5p is a fascinating miRNA that plays diverse roles in tumor suppression; it inhibits the invasion abilities of tumor cells by directly targeting PI3K/Akt, FAK, and KLF4 expression and may be a useful therapeutic target for the diagnosis and treatment of patients with glioblastoma (65)(66)(67). miR-20b inhibits the expressions of autophagy-related proteins that are induced by hypoxia/reoxygenation injury via ULK1 (68).…”
Section: Lncrna-mirna-mrna Network In Atii Cells Under Hypoxic Condit...mentioning
confidence: 99%